Evaluation of 30-Minute Office Blood Pressure in a Diverse Urban Population. (21st August 2021) - Philbrick, Ann M; Mahoney, Mélanie T; Harris, Ila M; Carlin, Caroline S; Fallert, Christopher
Abstract: BACKGROUND: Previous studies have shown benefits of 30-minute office blood pressure (OBP-30) but did not report on race and gender. The purpose of this study was to determine if similar effects are seen in a diverse urban population. METHODS: Patients with diabetes and/or cardiovascular disease (age 18–89) were invited to participate. Blood pressure was measured using standard procedure (SOBP). Patients were left alone in an exam room connected to an automated office blood pressure monitor which obtained BP readings every 5 minutes for 30 minutes. The last 5 measurements were averaged for the OBP-30 measurement. Primary outcomes were BPs measured using SOBP and OBP-30. Multivariate logit methods were used to estimate the average probability of having a BP measured <140/90 mm Hg (BPM <140/90) for the 2 measurement methods. Differences were computed across methods, in total and by sex and race, all other factors held constant. RESULTS: The adjusted probability of having a BPM <140/90 was 47.1% using SOBP and 66.7% using OBP-30 ( P < 0.01). Using SOBP, females had a 26.2 PP lower probability of having a BPM <140/90 ( P < 0.001) than males. Relative to white patients, Black patients had a 43.9 PP lower ( P < 0.001) and other races a 38.5 PP lower ( P < 0.001) probability of having a BPM <140/90 using SOBP. Using OBP-30, these differences narrowed and became statistically insignificant. CONCLUSIONS: OBP-30 may increase the probability of BPM meeting goals, especially in females and patients who are Black, indigenous, or persons of color. Graphical Abstract: